Management of mining wastes through their transformation into useful sorbent. Issue 1 (November 2021) - Grela, A; Łach, M; Korniejenko, K; Mierzwiński, D; Bajda, T; Hebda, M; Figiela, B
Abstract: Abstract Every year a few hundred million or so tons of industrial waste are generated all over Europe. A considerable share is attributable to exploratory wastes from the mining sector and combustion byproducts. The process of their reprocessing and utilization fits into the following rules subject to intensive development, viz.: zero waste economy (Zero Waste Europe), effective use of resources (Resource Efficient Europe) as well as closed-circuit economy (Circular Economy). The article shows some research results to corroborate the concept of industrial waste processing of carbonaceous shales into sorbent materials. The applied process of carbonaceous shale calcination led to the obtaining of a material containing metakaolinite, then used in the synthesis of zeolites. The specific surface of the sorbent obtained in the aforesaid way exceeded 100 m 2 /g.